Challenges in the management of an anuric child with end-stage renal disease since the neonatal period: a case report - Bieniek, Joanna; Zachwieja, Katarzyna; Miklaszewska, Monika; Drożdż, Dorota (Pediatria Polska - Polish Journal of Paediatrics, 2024)
End-stage renal disease requiring renal replacement therapy (RRT) since the neonatal period is a very rare condition. Peritoneal dialysis is the primary RRT in infancy. The case report describes a patient with congenital renal failure and anuria, abdominal wall laxity, small atrial septal defect, cryptorchidism, but without pulmonary hypoplasia or other disqualifying severe congenital defects. The patient had been dialysed since the fourth day of his life, until he received a kidney transplant at the age of 3.5 years. During RRT there were numerous complications related to dialysis catheter, infections, poor nutrition, and electrolyte abnormalities. It is a medical challenge to dialyse anuric children. Success requires a multidisciplinary team working towards the child’s proper growth as well as giving them a chance for a good quality of life.